Mekanisme Produksi Siaran Langsung dan Tidak Langsung Taping Radio dan TV Dalam Dakwah - Aulia Nur; Erwan Effendy; Muhammad Aidil Pratama; Nisya Aulia[ (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
The research aims to find out that da’wah isan activity that invites someone to do amar ma'ruf nahi mungkar to achieve the goal of happiness in the world and the hereafter through live broadcasts that record live broadcasts at the scene or in the field so that sometimes minimal errors are broadcast via TV and radio. And through indirect broadcasts with the production process which is usually recorded in advance or postponed for some time to do a series of edits so that it becomes a more interesting show and will later be broadcast via TV and radio or this is called taping. And this research uses a qualitative approach or descriptive method. Then observation here broadcasts at the scene or in the field so that sometimes minimal errors are broadcast via TV and radio. And through indirect broadcasts with the production process which is usually recorded in advance or postponed for some time to do a series of edits so that it becomes a more interesting show and will later be broadcast via TV and radio or this is called taping. And this research uses a qualitative approach or descriptive method. Then observation here is a way of collecting data which directly observes the research subject. This observation by looking at events in order to answer research. By looking at how the process of direct and indirect broadcasts that often occur in Indonesia. Keyword: live and indirect broadcasts, production process